Development of a Supply Chain Competitiveness Framework to Support the European Ocean Energy Sector (Proceedings of the European Wave and Tidal Energy Conference, 2025)
In 2023, the International Energy Agency’s technology collaboration programme on Ocean Energy Systems (IEA-OES) published a roadmap outlining how 300GW of ocean energy deployed globally by 2050, could result in $340bn in Gross Value Added (GVA) and 680,000 Full-Time Equivalent (FTE) jobs [1] to the global economy. At a European level, a recent ETIP Ocean report indicates that if Europe leads the global market in wave and tidal stream technologies, Europe could deploy 100GW of ocean energy by 2050, resulting in €140bn of GVA and 1.2 million new jobs by 2050[2].However, a significant determining factor in ensuring that Europe does lead this market, and secures the associated GVA and jobs, is the development of a highly-competitive, scalable and modernised pan-European supply chain. This factor has been acknowledged in a number of recent high-level European policy reports. The need for increased supply chain competitiveness in Europe is the primary consideration of the recent European Commission report, ‘The future of European Competitiveness’[3]. This issue is further examined by the ‘Align, Act, Accelerate’ European Commission report[4].While these reports aim to improve the overall competitive performance of the European economy with regards to the development of key industries and technologies, they do so from a non-sector specific perspective. Currently, there are no studies that examine the necessary steps required to improve the competitive performance of supply chains that support the future development of the ocean energy sector.Supported under the European Commission’s Horizon Europe EURO-TIDES project this paper, for the first time, will use a supply chain competitiveness framework to analyse in detail the areas of the supply chain most in need of policy intervention and financial support, to ensure that Europe continues to lead in the ocean energy market at a global scale. To deliver these outcomes, it will identify key supply chain areas and the opportunity that is represented by European manufacturing achieving a ‘Leading the Sector’ position. This will be done through the development of a novel supply chain competitiveness ranking framework, a draft of this is shown in Figure 1.For supply chain areas where a ‘Leading the Sector’ position is identified as a feasible and desirable outcome, this report will also put forward policy recommendations to help achieve this. These will be designed using a novel supply chain competitiveness framework that identifies the underlying factors that drive competitiveness across the European economy, with an early draft shown in Figure 2.The results of this study will be of interest to the scientific advisors, industry and government and will be vital in the design and delivery of targeted polices to support the European ocean energy sector.   References[1]          K. Grattan, H. Jeffrey, ‘Ocean Energy and Net Zero: An International Roadmap to Develop 300GW of Ocean Energy by 2050’, IEA-OES, 2023.[2]          ETIP Ocean, ‘A European Ocean Energy Industry - the €140bn Economic Opportunity’, 2022[3]          European Commission, ‘EU competitiveness: Looking ahead’, 2024[4]          European Commission, Align, act, accelerate: research, technology and innovation to boost European competitiveness, 2024